Umbrella Reviews Evidence Synthesis with Overviews of Reviews and Meta-Epidemiologic Studies - Biondi-Zoccai, Giuseppe (Springer International Publishing : Imprint: Springer, 2016)
This book is an ideal guide to umbrella reviews, overviews of reviews, and meta-epidemiologic studies for evidence synthesis. Research is conducted at different levels: primary research consists of original studies while secondary research comprises qualitative reviews, systematic reviews, and meta-analyses. Recently, a novel further level of research has been introduced, based on the analysis and pooling of reviews and meta-analysis. This book is the first to focus solely on this new type of research design, which permits a comprehensive and powerful synthesis of scientific evidence in medicine as well as in many other fields in order to inform decision-making. All aspects are covered, including review design and registration, the searching, abstracting, appraisal, and synthesis of evidence, the appraisal of moderators and confounders, and state of the art reporting. Case studies in a range of medical specialties are then presented. The hands-on approach of the book, written by a multinational team of experts, will enable the reader to interpret and independently conduct umbrella reviews.